HAART and the liver: friend or foe? - Pineda JA; Macías J; Mira JA; Merchante N; Valle J; Neukam KI (European Journal of Medical Research, 2010)
Abstract The overall effect of HAART on the liver is the result of the balance between hepatotoxicity and the consequences of immunoreconstitution on the evolution of HIV-associated liver diseases, particularly viral hepatitis. HAART may lead to the emergence of acute toxic hepatitis, steatosis, steatohepatitis, liver fibrosis, and noncirrhotic portal hypertension. On the other hand, HAART use has been associated with slower fibrosis progression in HIV/HCV-coinfected patients in most studies dealing with this issue. As well, an improvement of the clinical outcome of liver disease has been reported in patients taking HAART. For these reasons, the short- and mid-term effects of HAART on the liver are mostly beneficial.